Immunity to Vaccine-preventable Viral Infections in Australians Being Evaluated for Liver Transplantation. Issue 11 (November 2019) - Gardiner, Astrid; Liu, Ken; Bonnichsen, Mark; Joshi, Vikram; Davis, Rebecca J.; Strasser, Simone I.
Abstract : Background: Vaccine-preventable viral infections are associated with increased risk of morbidity and mortality in immunocompromised patients. Current guidelines recommend routine screening and vaccination of all patients before solid organ transplantation. We studied rates of immunity against vaccine-preventable viruses in liver transplantation (LT) recipients. Methods: We retrospectively studied consecutive adult patients who underwent first deceased donor LT at a single center between August 2008 and October 2017. Viruses studied were hepatitis A (HAV), hepatitis B (HBV), varicella zoster virus (VZV), measles, and mumps. Hepatitis B surface antibody (anti-HBs) <10 IU/mL in HBV surface antigen-negative patients and negative IgG to other viruses was regarded as absent immunity. Results: Five hundred and fifty-five patients underwent LT (72.4% male; median age, 55.0 y). Percentages of patients who lacked immunity to vaccine-preventable infections were HAV (31.8%), HBV (63.8%), measles (1.4%), mumps (6.6%), and VZV (3.8%). Age was positively associated with immunity (from either past exposure or vaccination) against most viruses, including HAV, measles, mumps, and VZV ( P < 0.05 for all). In contrast, older age was marginally associated with anti-HBs <10 IU/mL ( P = 0.046). No significant changes in immunity rates were observed during the study period. Conclusions: A substantial number of patients undergoing LT are not immune to vaccine-preventable viruses at the time of assessment. This presents an opportunity for pre-LT vaccination and in particular younger patients may need to be targeted.